Embedded health risk from arsenic in globally traded rice - Nunes, Luís (2022)
International food trade is fundamental to globalfood security but with often negative consequences in theproducing country. We propose a method of quantifyingflows ofinorganic arsenic (iAs) and embedded increased lifetime cancerrisks (EHR) at a global scale, where negative impacts are felt onthe importing country. Computations were made for 153countries. Vietnam exports the most iAs embedded in rice (796kg/year) followed by India (788 kg/year), Thailand (485 kg/year),and the United States (323 kg/year). We show that continentalChina, Indonesia, and Malaysia have the highest imports of iAs(292, 174, and 123 kg/year, respectively). Bangladesh rankshighest in EHR followed by Vietnam and Cambodia (150, 141, and 111 per 100,000, respectively). Countries that dependexclusively on imported rice are importing a substantial amount of risk, as, e.g., Kiribati and Solomon Islands (57 and 53 per100,000, respectively). We discuss the potential policy options for reducing population dietary health risks by well-balancedapportioning of rice sources. This study targets policy design solutions based on health gains, rather than on safe levels of the riskfactor alone.